Identifikasi Titik Rawan Kecelakaan (Black Spot) Pada Ruas Jalan Tjilik Riwut Palangka Raya Sebagai Infrastruktur Penunjang Menuju IKN Nusantara: Identification Of Accident-Prone Points (Black Spots) On The Tjilik Riwut Palangka Raya Road Section As Supporting Infrastructure Towards The Archipelago's IKN - Antoni, Bram Wira; Basuki, Imam (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Palangka Raya is the capital of Central Kalimantan province as a connecting city to the National Capital of the Archipelago. As a hub city, it is important to review infrastructure and security readiness. Jalan Tjilik Riwut Km 1 - Km 10 is the main road section as a cross-provincial route to IKN which often has accidents so further analysis needs to be carried out. The aim of this research is to determine the characteristics of traffic accidents and determine black spots on the Tjilik Riwut road Km 1 - Km 10, Palangka Raya city as well as appropriate recommendations. The method used is the Equivalent Accident Number (EAN) or Accident Equivalent Number (AEK). The characteristics of accidents on the Tjilik Riwut road section are that the majority occur at Km 1.5, with the most incidents in 2019, the most types of vehicles are MC, with a single accident, the nature of the road is straight, the majority of accidents are male, mature age and type of work private. The majority of accidents are due to entering and leaving the market and the sudden wide median at Km 1. The black spot location in this study, namely at Km 1+000 to 1+999, has a total of 65 accidents with an Accident Equivalent Number (AEK) of 304 which is which exceeds the specified Upper Control Limit (BKA) number (136.2). Recommendations that can be made are adding a Rumble Strip to reduce vehicle speed and changing the design of the road median to create a smoother transition from small to large.